2020
DOI: 10.1186/s13063-020-04734-z
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent plasma transfusion therapy in severe COVID-19 patients- a safety, efficacy and dose response study: A structured summary of a study protocol of a phase II randomized controlled trial

Abstract: Objectives General: To assess the safety, efficacy and dose response of convalescent plasma (CP) transfusion in severe COVID-19 patients Specific: a. To identify the appropriate effective dose of CP therapy in severe patients b. To identify the efficacy of the therapy with their end point based on clinical improvement within seven days of treatment or until discharge whichever is later and in-hospital mortality c. To assess the clinical improvement after CP transfusion in severe COVID-19 patients d. To assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Convalescent plasma (CP) from patients who recover from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been in use since the inception of the pandemic to treat Coronavirus Disease 2019 (COVID- 19) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Discrepant reports of the efficacy of treatments for COVID-19, including CP, emerged from a rapidly evolving political and interventional landscape of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Convalescent plasma (CP) from patients who recover from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been in use since the inception of the pandemic to treat Coronavirus Disease 2019 (COVID- 19) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Discrepant reports of the efficacy of treatments for COVID-19, including CP, emerged from a rapidly evolving political and interventional landscape of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The searches of clinical trial registries for eligible studies under way or planned to investigate the use of CP for COVID-19 during pregnancy were negative. The three protocols for a randomized controlled trial we found during our online search of databases [ 28 , 29 , 30 ] excluded pregnant women from the design.…”
Section: Resultsmentioning
confidence: 99%
“…Recent results from studies on a large population of critically ill patients show that CP is potentially effective and sufficiently safe in hospitalized patients with COVID-19. Several clinical trials are ongoing to assess safety, efficacy, appropriate effective dose, and dose-response of CP transfusion in COVID-19 patients and to specifically define clinical and laboratory improvements after CP [ 125 , 126 , 127 , 128 , 129 ]. However, no definitive demonstration of a beneficial effect is available, as recently reported [ 119 ].…”
Section: Passive Immunotherapy and Covid-19: Ivig Convalescent Plmentioning
confidence: 99%